Respuesta :

Answer:

[tex]\mathbf{(\overline x , \overline y ) = (\dfrac{5}{8}, \dfrac{5}{14})}[/tex]

Step-by-step explanation:

Given that:

[tex]y = x^{2/3}[/tex] at y = 0 , x = 1

Then:

Area = [tex]\int^{1}_{0} x^{2/3} \ dx[/tex]

Area = [tex]\begin {bmatrix} \dfrac{3}{5}x^{5/3} \end {bmatrix} ^1_0[/tex]

Area = [tex]\dfrac{3}{5}[/tex]

Then:

[tex]\overline x = \dfrac{1}{A} \int^b_a x (f(x) -g(x) ) \ dx[/tex]

[tex]\overline x = \dfrac{5}{3} \int^1_0 x (x^{2/3} -0 ) \ dx[/tex]

[tex]\overline x = \dfrac{5}{3} \int^1_0 x^{5/3} \ dx[/tex]

[tex]\overline x = \dfrac{5}{3} \ [\dfrac{3}{8}x^{8/3}]^1_0[/tex]

[tex]\overline x = \dfrac{5}{3} \times \dfrac{3}{8}[/tex]

[tex]\overline x = \dfrac{5}{8}[/tex]

Similarly;

[tex]\overline y = \dfrac{1}{A} \int^b_a \dfrac{1}{2} \begin{bmatrix} (f(x)^)2 - (g(x))^2 \end {bmatrix} \ dx[/tex]

[tex]\overline y = \dfrac{5}{3} \int^1_0 \dfrac{1}{2} \begin{bmatrix} (f(x^{2/3})^2 -0 \end {bmatrix} \ dx[/tex]

[tex]\overline y = \dfrac{5}{3} \int^1_0 \dfrac{1}{2} \begin{bmatrix} (x^{4/3} ) \end {bmatrix} \ dx[/tex]

[tex]\overline y = \dfrac{5}{3} \begin{bmatrix} \dfrac{1}{2} (x^{7/3} ) \times \dfrac{3}{7} \end {bmatrix} ^1_0[/tex]

[tex]\overline y = \dfrac{5}{3} \begin{bmatrix} \dfrac{3}{14} (x^{7/3} ) \end {bmatrix} ^1_0[/tex]

[tex]\overline y = (\dfrac{5}{3} \times \dfrac{3}{14} )[/tex]

[tex]\overline y = \dfrac{5}{14}[/tex]

Thus; [tex]\mathbf{(\overline x , \overline y ) = (\dfrac{5}{8}, \dfrac{5}{14})}[/tex]

ACCESS MORE